Efektivitas berbagai jarak jangkau aplikasi ulv-malathion terhadap aedes aegypti di kecamatan sewon, bantul=The Effectivity of Various Distances at the Application of IILV-Malathion Against Aedes aegypti at Sewon Distric - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
.Malathion is still used in the National Program of Dengue Vector Control in Indonesia, which is applied either in the form of cold aerosols (ULV) or thermal fog. This study aimed at determining the effectivity of ULV application of malathion with different distances against Aedes aegypti in Sewon District, Bantul (Prov. DIY). Methods of the study included the use of adult Aedes aegypti of laboratory strain. The mosquitos placed at distances of 35 & 70 meters from the nozzel of ULV-machine. The experimental unit was 20 mosquitos per-cage treated with three replicates respectively in two sub village (dusun)